2020
DOI: 10.1080/24750263.2020.1747558
|View full text |Cite
|
Sign up to set email alerts
|

Shedding light upon the complex net of genome size, genome composition and environment in chordates

Abstract: The nucleotype theory has been advanced on the basis of studies regarding genome size and composition in various plant and animal species, i.e. the influence that genome can have on the phenotype independently of the informational content of DNA. It has also been noted that during evolution various interactions between different environmental factors and genome structural and functional parameters would have occurred. In this review, changes in genome size, transposon content, and base composition occurred dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…Overall, the activity of TEs can increase due to environmental stressors such as temperature 22 . In particular, the beginning of Carboniferous and the transition from Permian to Triassic were characterized by severe environmental changes 56 that might have provoked a reduction of the efficiency of silencing mechanisms in gonads, leading to a mobilization of TEs and thus to an increase of genome size in lungfish and newts 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the activity of TEs can increase due to environmental stressors such as temperature 22 . In particular, the beginning of Carboniferous and the transition from Permian to Triassic were characterized by severe environmental changes 56 that might have provoked a reduction of the efficiency of silencing mechanisms in gonads, leading to a mobilization of TEs and thus to an increase of genome size in lungfish and newts 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Even though several factors, such as metabolic rate and cell cycle duration, have been associated with amphibian genome size 8 , 16 , 17 , the molecular mechanisms favouring the persistence of extreme repetitive DNA contents in salamander genomes remain to be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Despite many attempts to find abiotic and biotic factors that contribute to the enormous natural variation in genome size, it remains an open question which evolutionary and ecological variables drive genome size changes (Blommaert 2020). The main challenges to resolving this question arise from the complexity of genome composition, decoupling the role of selection (if present) from many different environmental factors, and the dependence of genome size on phylogenetic relatedness (Alfsneset al 2017;Canapa et al 2020;Ritchie et al2017). Recent studies have shown that the genome size is positively correlated with the size of repetitive DNA in insects (Quesneville 2015), but repetitive DNA has been linked to both adaptive and non-adaptive evolutionary processes (Canapa et al 2015;Loweret al 2017).…”
Section: Genome Structure and Signatures Of Cold Specialization In Beetlesmentioning
confidence: 99%
“…Moreover, transposons can be co-opted and exapted, creating regulatory sequences, coding exons, or entirely new genes useful for the host genome [ 22 , 23 , 37 , 205 ]. Indeed, a great number of reports have suggested the responsiveness and susceptibility of TEs to environmental changes or stressful conditions [ 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 ]. Yuan and colleagues [ 31 ] analyzed 52 fishes and reported an increase in the DNA transposons in bony fish living in freshwaters and an abundance of tandem repeats in marine species that was not explained by phylogenetic relationships.…”
Section: Fish Transposons and The Environmentmentioning
confidence: 99%